Sociodemographic Determinants of Self-reporting Mental Health Problems in Indonesian Urban Population - Purba, Fredrick Dermawan; Fitriana, Titi Sahidah (UI Scholars Hub, 2019)
Studies have found that mental health problems are more prevalent in urban areas compared to rural ones, including in Indonesia. About 6% of Indonesian people report having mental health problems, and 1.7 out of every thousand residents are diagnosed with a psychiatric problem. This study examines the sociodemographic determinants of reporting mental health problems among Indonesia’s general population living in urban areas. One thousand forty participants aged 17 years and over answered sociodemographic questions (i.e., residence, gender, age, education level, income, marital status) and completed the EQ-5D-5L. Their responses to the Anxiety/Depression item of the EQ-5D-5L (no problem vs. any level of problem) were the dependent variable sociodemographic factors were the explanatory variables. About one-third (35.37%) of the participants reported experiencing problems with anxiety/depression. Logistic regression found that marital status was significantly associated with reporting any problems of anxiety/depression in the EQ-5D-5L: single/divorced participants were 58% more likely to report that they suffered from anxiety/depression in comparison to their married counterparts. These results highlight the importance of social support; that is, having a spouse or extended family member whom one can count on for help when facing a problem is essential, regardless of one’s gender, age, educational level, or income.